Effect of welding and complex loads on the high-strength steel T-stub connection. (November 2018) - Sun, Fei Fei; Xue, Xuan Yi; Xiao, Yong; Le, Yü Min; Li, Guo Qiang
Abstract: After welding, a heat affected zone (HAZ) is formed in the area near a weld toe. The main microstructure is composed of high-strength steel (HSS) that is not stable at high temperatures. Therefore, it is necessary to investigate whether EC3 formulae based on examining a mild steel T-stub can be used to design an HSS T-stub. In the study, an experiment with two groups of Q690 T-stubs was performed. The results indicate that the EC3 formulae cannot be directly used to design the HSS T-stub. The effect of HAZ was further investigated by performing a finite element analysis (FEA). With respect to the specimens in the study, the factor χ HAZ that represents the effect of HAZ is quantified by using the results of the experiment and FEA. The modified EC3 method2 was validated to accurately predict the first yield resistance of HSS T-stub. The T-stub is subjected to combined axial and shear loads. The relation between transversal and axial displacements of the T-stub under combined axial and shear loads was established. The effect of combined axial and shear loads on the connection behavior of the HSS T-stub was examined through the FEA. The result shows that the ductility of the T-stub under combined axial and shear loads is lower than that of the T-stub under axial load. We introduce a factor χ CL to propose a formula to predict the first yield resistance of HSS T-stub by considering the effect of combined axial and shear loads. Highlights: An experiment of HSS T-stub specimens and FEA are performed to investigate the softening effect of HAZ and complex loads on connection behavior.